EXAMINATION OF STUDIES REGARDING PRE-SERVICE EFL TEACHERS’ TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) IN TURKEY - Emrah EKMEKÇİ (International Journal of Eurasia Social Sciences, 2018)
One of the sets of skills most in demand in the 21st century is information, media, and technology skills. In addition to these most demanded skills, qualified teachers are expected to master pedagogical and content knowledge as well. For this reason, teachers’ competencies with regard to their technological, pedagogical and content knowledge (TPACK) have been the subject of much debate in recent years. This study aims to analyse studies on pre-service English as a Foreign Language (EFL) teachers’ TPACK competencies in Turkey. The study employs meta-synthesis method to present current TPACK competencies of pre-service EFL teachers and to find out the research tendency as to TPACK of pre-service EFL teachers in Turkey. To this end, 3 dissertations and 12 articles between the years of 2005-2018 have been analysed in terms of aims, method, subject group, and findings. The articles and dissertations have been reached through searching databases with certain keywords. ERIC, EBSCHOHost, Web of Science, Google Scholar, Springer, TÜBİTAK ULAKBİM Dergipark, and YÖK National Dissertation Center have been used as research databases in the study. The results of the study reveal that research investigating TPACK of pre-service EFL teachers mainly focus on development of TPACK over time, the effect of TPACK-based treatment, gender, and academic achievement, development of TPACK self-assessment survey, comparison of TPACK among pre-service, in-service, and formation program students, and finally TPACK and its reflections on lesson planning. It is also concluded that although pre-service EFL Teachers’ TPACK competencies in Turkey seem to be highly developed in the studies, more descriptive and experimental studies are required to have a satisfactory perspective of the current competence levels of the students.